2018
DOI: 10.1186/s12906-018-2247-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evaluation of anti-inflammatory activity of phenolic lipid extracted from cashew nut shell liquid (CNSL)

Abstract: BackgroundAnacardium occidentale L phenolic lipid (LDT11) is used in traditional medicine as anti-inflammatory, astringent, antidiarrheal, anti-asthmatic and depurative. Phenolic derivatives, such as anacardic acid, extracted from cashew nut shell liquid (CNSL) have demonstrated biological and pharmacological properties, and its profile makes it a candidate for the development of new anti-inflammatory agents.The objective of the present study was to evaluate the anti-inflammatory profile of a derivative, synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Cashew nut shell phenolics are used in traditional medicine as anti-inflammatory, antidiarrheal, anti-asthmatic and depurative agents. Previous studies have confirmed their biological properties, including antibacterial, anti-inflammatory, antiproliferative, antioxidant and enzymatic inhibitory activities (de Sousa Leite et al, 2016;de Souza et al, 2018). Chen et al (2005) reported on the extracted almond skin flavonoids and demonstrated their antioxidant capacity in vitro.…”
Section: Health Benefits Of Phenolic Compoundsmentioning
confidence: 80%
“…Cashew nut shell phenolics are used in traditional medicine as anti-inflammatory, antidiarrheal, anti-asthmatic and depurative agents. Previous studies have confirmed their biological properties, including antibacterial, anti-inflammatory, antiproliferative, antioxidant and enzymatic inhibitory activities (de Sousa Leite et al, 2016;de Souza et al, 2018). Chen et al (2005) reported on the extracted almond skin flavonoids and demonstrated their antioxidant capacity in vitro.…”
Section: Health Benefits Of Phenolic Compoundsmentioning
confidence: 80%
“…The cashew nuts contain phenolic compounds with antioxidant activity [19,44] and can be used to treat the incidence of chronic and degenerative diseases, including cancer, cardiovascular and neurodegenerative diseases [39]. CNSLs have been also reported for many other diverse pharmacological effects such as insecticidal [13], larvicidal and antiacetylcholinesterase [7,34], anti-inflammatory [8], antioxidant [3], anxiolytic [14], antibacterial [27], and so on. In a recent study, it has been reported that the CNSLs may impart genotoxic effects in prokaryotic and eukaryotic systems [24].…”
Section: Introductionmentioning
confidence: 99%
“…The stem bark, fruits, and leaf extract, have pharmaceutical properties and extensively used as antiin ammatory, antioxidant, antibacterial, and antidiarrheal [13][14][15][16]. The anti-diabetic and anti-in ammatory properties have also been reported [17].…”
Section: Introductionmentioning
confidence: 99%